Itolizumab, an anti-CD6 monoclonal antibody, as a potential treatment for COVID-19 complications - Loganathan, Subramanian; Athalye, Sandeep N.; Joshi, Shashank R. (Expert opinion on biological therapy, 2020)
The globally rampant SARS CoV-2 pandemic requires novel medical strategies to control the severity of disease and death due to complications. Of the 15-20% patients that develop pulmonary symptoms, a sub-set develops an acute respiratory distress syndrome (ARDS) rapidly progressing into a critical condition. Marked elevation of cytokines/chemokines is observed with elevation of additional markers of inflammation, coagulation, and organ damage such as CRP, D-dimer, LDH, Ferritin and Troponin-I. This hyperinflammation leads to worsening of oxygen saturation due to pulmonary infiltration and exudation, organ damage, and dysfunction of coagulation pathway and may lead to multi-organ failure. The role of anti-inflammatory monoclonal antibodies such as Itolizumab, in cytokine storm. Itolizumab, an anti-CD6 humanized IgG1 mAb, binds to domain-1 of CD-6 that is responsible for priming, activation, and differentiation of T-cells. Itolizumab significantly reduces T-cell proliferation along with substantial downregulation of the production of cytokines/chemokines. Approved for moderate to severe chronic plaque psoriasis in 2013 it is currently being studied for addressing COVID-19 related cytokine storm and its complications. This article reviews its use in COVID-19 infections; its dose, administration protocol, contra-indications, and safety in treating moderate-to-severe ARDS by preventing and treating the cytokine storm and its complications.